Mechanical contraction patterns of the systemic right ventricle: a 3D echocardiography study. (8th February 2021) - Surkova, E; Kovacs, A; Bispo, D; Flick, C; Lakatos, BK; Tokodi, M; Liptai, C; Fabian, A; Merkely, B; Senior, R; Gatzoulis, M; Li, W
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. In patients with transposition of great arteries (TGA) post atrial switch operation or with congenitally corrected TGA (ccTGA), the morphologically right ventricle (RV) has to adapt to the chronically increased systemic pressure. Purpose. To investigate the functional adaptation of the systemic RV in patients with TGA post Mustard repair or ccTGA. Methods. RV volumes and EF were measured by 3D echocardiography in 33 patients with the systemic RV (21 TGA and 12 ccTGA; 45 ± 13y, 61% male), and in 33 healthy volunteers (44 ± 13y, 61% male). The 3D RV model was postprocessed by the ReVISION software and its contraction was decomposed along the longitudinal, radial and anteroposterior directions (Fig.A, Systemic RV in TGA) providing longitudinal, radial and anteroposterior EF (LEF, REF and AEF). Relative contribution of each component was measured as the ratio between LEF, REF and AEF to the global RVEF (LEFi, REFi and AEFi). Results. Systemic RV was significantly larger with reduced function compared to controls (Tab). 3D RVEF demonstrated stronger correlation with BNP (Rho -0.76, p < 0.0001) compared to other parameters of RV function (free wall strain 0.55, p = 0.0083; FAC -0.47, p = 0.024; S' -0.39 and TAPSE 0.06, p > 0.05). While in healthy volunteers, all 3 components of RV systolic function contributed equally to the global RV EF, in patients with TGA the relative contribution of the anteroposterior component was dominant and differed significantly from longitudinal and radial components (AEFi 0.48 ± 0.06 vs LEFi 0.31 ± 0.07 vs REFi 0.36 ± 0.09, p < 0.0001)(Fig. B, C). In patients with ccTGA the longitudinal component was dominant and provided a relative compensation for the reduced anteroposterior and radial components (LEFi 0.47 ± 0.07 vs AEFi 0.34 ± 0.07, p = 0.0002 and vs REFi 0.36 ± 0.09, p = 0.0023)(Fig. B, C). Relative contribution of the radial contraction was significantly reduced in all systemic RV patients. Conclusions. Systemic RV contraction patterns change significantly with anteroposterior contraction being dominant in patients with TGA post Mustard repair and longitudinal component being dominant in ccTGA. 3DE should be a part of routine assessment of the systemic RV, especially in TGA since no conventional echo parameters take into account anteroposterior RV contraction.